Anomalous optical response of graphene on hexagonal boron nitride substrates - Adilet N. Toksumakov; Georgy A. Ermolaev; Mikhail K. Tatmyshevskiy; Yuri A. Klishin; Aleksandr S. Slavich; Ilya V. Begichev; Dusan Stosic; Dmitry I. Yakubovsky; Dmitry G. Kvashnin; Andrey A. Vyshnevyy; Aleksey V. Arsenin; Valentyn S. Volkov; et al. (Communications Physics, 2023)
Two-dimensional materials look poised to revolutionize information and communication technologies. Here, the authors leveraged spatially resolved ellipsometry to engineer the optical absorption of graphene on hexagonal boron nitride substrates, thereby disclosing effective solutions for flexible optoelectronics.